Caregiver, child and family characteristics associated with parenting stress in rural KwazuluNatal - Mitchell, Joanie (Department of Psychology, 2020)
Parenting Stress (PS) has been shown to negatively impact on various areas of child development. Additionally, clinically significant levels of PS have been shown to be fairly stable over time and thus unlikely to decrease without intervention. Understanding factors that contribute to PS is therefore important for developing preventative interventions. Despite this, PS has largely been understudied, particularly in low- and middle-income countries (LMICs). The present study aimed to explore PS among 1535 caregivers of primary school-aged children in rural KwaZulu-Natal. The data were collected by experienced fieldworkers, in interviewer style, over three visits, and underwent checks for completeness and quality assurance, prior to data entry. The analysis for the present study included using logistic regression techniques to examine contributing caregiver, child and family factors, as well as content analysis to examine caregivers’ most prominent concerns about their children. Around 16% of this sample were experiencing clinically significant PS. The following factors were found to increase risk of PS: the mother becoming HIV infected post-pregnancy, the family experiencing recent food insecurity, the child exhibiting internalizing or externalizing behaviours and the child having academic or other problems at school. Two factors were linked to a reduced likelihood of PS, namely the child being helped to learn shapes and sizes at home and maternal participation in a breastfeeding study. The content analysis revealed that caregivers most frequently reported having psychosocial concerns about their children, including specific personality traits such as low levels of conscientiousness and poor self-regulation. These findings illustrate the need for early intervention and support for mothers and children in LMICs. Furthermore, this research showed the impact of parental HIV and the need for comprehensive life-course approaches to curb future adversities for HIV infected women and families.